The negative impact of riba banking on the performance of Islamic banking in a dual banking system - Muhammad Zahid Abdul Aziz (Institute of Islamic Banking & Finance, International Islamic University Malaysia, 2012)
Islamic banking is now an established part of many nations' banking system so much so it is said to be operating in a dual system alongside conventional banking. This duality is particularly emphasised in Malaysia and even recognised by the nation's central banking legislation. However this duality is not such an innocuous situation and is suspected by the researcher to be a principal reason for many of the weaknesses found in Islamic banking today. That Islamic banking is criticised for many deficiencies is a widespread phenomenon these days. These includes it being a mirror image of conventional banking, tenuous in terms of Shariah compliance; fails to meet Maqasid Shariah, do not aid equitable distribution of wealth and manages risk like a money lender. The reasons attributed include it being too focussed on debt financing, weaknesses oflslamic bankers, and impiety of the ummah. No studies have sought to identify the coexistence of conventional banking as a factor directly contributing to these weaknesses of Islamic banking. No studies have examined the environment Islamic banking is expected to be operating in as compared to the environment it found itself in. No studies have examined whether the regulatory measures imposed on conventional banking is correct when imposed on Islamic banking. This study aims to fill that gap. This study articulates that conventional banking is negatively impacting the performance of Islamic banking, in particular on Islamic banking's ability to uphold true compliance with Shariah. It is hoped that this study will trigger similar studies to further prove its findings. It is the unashamed hope of the researcher that one day Muslim nations can bury riba banking and build on its ashes a sole and single Islamic banking system that upholds and embodies the true demands of the Quran and Sunnah.